A Non-Ciliary Receptor in the Mandible of a Mystacocarid Crustacean, Derocheilocaris Typica. Issue 4 (1st July 2015) - Elofsson, Rolf
Abstract: The mystacocarid crustacean Derocheilocaris typica Pennak and Zinn, 1943 lives in sand interstices and is less than one mm long. It is unique among Arthropoda. It has sensory cells in the mandible, which lack cilia. The function as mechano- and/or chemo-receptors has been replaced by dendrites, the sensory cell protrusions carrying cilia. The dendrites swell, flatten, and fill the endite – a medial outgrowth from the mandible, which is the main masticating appendage. The dendrites have many contacts with the inside of the cuticle, which insures close proximity to the food outside the body. Another feature specific to D. typica is the reduced cilia in the cuspidate setae of the food handling appendages: first and second maxillae, and maxilliped. The remaining approximate 50 setae on the body, not related to food handling, conform to those of all arthropods.